Effect of feed composition and operating conditions on quality of spray-dried coconut milk powder - Mazlina Muhad Maran (2017)
Spray drying of coconut milk had been carried out to study the effect of the inlet temperature and the feed concentration on the production yield, moisture content and particle size of the coconut milk powder. The coconut milk used are pure coconut milk obtained from extraction of grated coconut. The drying agent that have been used are Maltodextrin DE. Coconut milk were spray dried with inlet temperature of 140°C, 150°C and 160°C meanwhile the concentration of feed were 10%, 15% and 20%. For 10% feed concentration with increasing inlet temperature resulted in decreasing of production yield but raised of the moisture content and particle size of the coconut milk powder. The increase of feed concentration from 10% to 20% with the fixed inlet temperature at the 160°C cause the increasing in moisture content and production yield but decrease in particle size. Optimization has been carried out in order to select the optimum parameters to obtain the best quality of coconut milk powder. The physical property that been focused on for optimization process is moisture content the optimized value are 160°C inlet temperature and 20% feed concentration. The optimized process are carried by using Design Expert 6.0. The validation of the data also have been carried out in this research. The estimated moisture content are 4.77724%. Meanwhile from the experiment, the moisture obtained are average 5.15%. Hence, the percentage error of this data are 7.34%.
Project paper (B.E. (Engineering Process and Food) - Universiti Putra Malaysia, 2017.